The frameworks of English : introducing language structures - Ballard, Kim. (New York : Palgrave Macmillan, 2013)
"How does language work? What are the different elements? How do they all fit together? The Frameworks of English is a step-by-step guide through the various levels of language, describing the morphological, lexical, grammatical and phonological frameworks of contemporary English in a clear and logical way. Beginning with words as the building blocks of language, it investigates their internal structure and shows how words can be combined into larger and larger units, from phrases to sentences and beyond. The sound system of language is explored, covering the production of individual sounds as well as the features of syllable structure and connected speech. The third edition of this popular textbook: [bullet] features a new chapter on how to approach accent and dialect variation in English throughout the world [bullet] includes both spoken and written examples of electronically mediated language [bullet] offers updated suggestions for further reading and research [bullet] contains an expanded glossary of linguistic terminology to aid study With plenty of exercises and helpful cross-referencing The Frameworks of English covers everything that you need to know about linguistic structures"--
Machine generated contents note: -- List of Tables -- List of Figures -- Acknowledgements and Sources -- PART I: INTRODUCTION -- 1. Introduction -- PART II: LEXICAL FRAMEWORKS -- 2. Word Classes -- 3. Word Formation -- PART III: GRAMMATICAL FRAMEWORKS -- 4. Inflections -- 5. Phrases -- 6. Clauses -- 7. Sentences -- PART IV: DISCOURSE FRAMEWORKS -- 8. Beyond Sentences -- PART V: PHONOLOGICAL FRAMEWORKS -- 9. Phonetics and Phonemes -- 10. Segmental Phonology -- 11. Suprasegmental Phonology -- PART VI: BROADER PERSPECTIVES -- 12. Variation in English -- 13. Phonetic and Other Symbols -- 14. Answers to Exercises -- Glossary -- Index.
Keywords: English language -- Grammar; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; LANGUAGE ARTS & DISCIPLINES / Linguistics / Syntax